20 questions: Evidence-based practice or sacred cow?. Issue 8 (August 2015) - Miller, Julie; Hayes, Denise Drummond; Carey, Katherine W.
Abstract : Despite dramatic advances in healthcare research, many nurses continue to promote outdated nursing practices. Grounded in tradition rather than science, these "sacred cows" are ineffective, unnecessary, and sometimes dangerous. Read the results of a nationwide survey designed to test nurses' knowledge and beliefs about outdated nursing practices, then update your practice based on the best evidence available.